How and why non-profit organizations use social media in their marketing strategy?: A case study of global non-profit organization: United Nations Children's Fund - Maxhuni, Nora (My University, 2021)
The emerged popularity of social media has remarkably transformed the way how non-profit organizations communicate, interact, create and share information with their audience. During past years, the attention and interest of social media have increased among non-profit organizations. The concept of social media is developing and new types of media are continuously appearing at rapid pace. However, we lack research regarding the adoption and usage of social media by non-profit organizations. Therefore, the purpose of this thesis is to understand how and why non-profit organizations use social media in their marketing strategy. The objective of the thesis is reached through semi-structured interviews with global non-profit organization, United Nations Children’s Fund functioning in Finland and Kosovo. In total, five interviews were conducted with employees. In terms of the research approach, the inductive approach is adopted and presented, and collected data were evaluated through thematic analysis. The thesis depicts that social media has become a very effective tool to improve the marketing performance of non-profit organizations. Additionally, it has resulted that social media plat-forms such as Facebook, Instagram, and Twitter enable non-profit organizations to increase their brand awareness, loyalty, and reputation, share information, reach a wider range of audience, build relationships, reduce communication and marketing costs, promote advocacy work and raise funds. This thesis results that non-profit organizations should consider different social media types as a marketing tool since there have revealed many benefits of using social media.
Keywords: social media; marketing; non-profit corporations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business